2020
DOI: 10.1002/jaba.675
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the reinforcing efficacy of tokens and primary reinforcers

Abstract: Token economies are one of the most commonly used behavior‐analytic interventions. Despite literature supporting the use of tokens as tools for behavior change, little is known about the efficacy of tokens compared to that of the items for which they are exchanged. Results of previous research comparing the reinforcing efficacy of tokens and primary reinforcers have shown that both produce similar effects on responding. However, published findings have been confounded given the inclusion of primary reinforcers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Applied research has generally supported the notion that reinforcer quality affects treatment efficacy, but comparatively little applied research has examined how reinforcer quality affects relapse susceptibility. However, Norris and Greer (2023) recently showed that individuals whose severe problem behavior is maintained by multiple reinforcers (e.g., access to attention and toys) often have strong preferences for one functional reinforcer over others. The extent to which the maintenance of problem behavior by qualitatively distinct reinforcers affects treatment efficacy and relapse susceptibility has yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Applied research has generally supported the notion that reinforcer quality affects treatment efficacy, but comparatively little applied research has examined how reinforcer quality affects relapse susceptibility. However, Norris and Greer (2023) recently showed that individuals whose severe problem behavior is maintained by multiple reinforcers (e.g., access to attention and toys) often have strong preferences for one functional reinforcer over others. The extent to which the maintenance of problem behavior by qualitatively distinct reinforcers affects treatment efficacy and relapse susceptibility has yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most studied types of token are those providing some sort of incentive or reward; these serve as reinforcement mechanisms in token economies (e.g. Bonfonte (2020), Ivy (2017), Doll (2013)). Such tokens may be tangible: gaming chips, coins, tickets, stickers, marbles, or stamps (McLaughlin & Williams, 1988).…”
Section: Literature Background 31 Physical and Digital Tokensmentioning
confidence: 99%
“…Given the frequent use of token systems, understanding the relative reinforcing value of tokens compared with the items for which they are exchanged is important (Fiske et al, 2015). Tokens may be more valuable than the back-up reinforcers because they can be arranged as generalized conditioned reinforcers, or they may be less valuable due to delayed access to the back-up reinforcers (Bonfonte et al, 2020). Recently, a few investigations have assessed the value of tokens compared with the items for which they are exchanged.…”
mentioning
confidence: 99%
“…Bonfonte et al (2020) also evaluated the reinforcing value of tokens using a progressive‐ratio (PR) reinforcement schedule with two young men diagnosed with ASD. The researchers used PR schedules to compare the efficacy of tokens (exchangeable for edible items) to high‐ and low‐preference edibles used as primary reinforcers.…”
mentioning
confidence: 99%
See 1 more Smart Citation